The agrifood question and rural development dynamics in Brazil and China: towards a protective ‘countermovement’ - Escher, Fabiano; Schneider, Sergio; Ye, Jingzhong (Globalizations, 2018)
This paper explores some features of the development paths taken by Brazil and China (two member countries of the BRICS grouping) in the current context of the crisis of neoliberal globalization and transformation of the political and economic world order. The authors use Polanyi’s ‘double movement’ thesis to argue that newly emerging rural development (RD) dynamics in China and Brazil are part of a protective ‘countermovement’, driven by actors and institutions responding to the contradictions of the concentration and internationalization of agrifood systems. However, thedirectionand scope of these countermovements are still open; their transformative potential should be viewed in Gramsci’s terms as a struggle for hegemony the outcome of which depends on the concrete ‘balance of social forces’. First, the paper characterizes the impacts of China’s rise on Brazil’s development, which subsequently found its economy under threat of reprimarization and deindustrialization. The paper then sketches some stylized facts of production and consumption within the Brazil–China soy–meat complex, a key element of the current global food regime, with a focus on corporate control of the soy–meat value chain, and its negative consequences. Finally, the paper identifies the key roles that actors and institutions linked to peasants and family farmers are playing in the RD dynamics of each country. Although China and Brazil represent two very different realities, the comparison shows that critical rural and agrifood issues are indeed moving onto the centre stage of the contemporary ‘double movement’.
Sociology; Rural Studies
Keywords: Brazil; Brazil–China soy–meat complex; China; deindustrialization; double movement; farming practices; food industry; globalization; production–consumption relations; rural development; rural policies